2002
DOI: 10.1039/b208422h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, chiroptical properties and absolute configuration of spiro[1,3-benzodioxole-methanocyclooct[b]indole]

Abstract: The synthesis of chiral 1'H-spiro[1,3-benzodioxole-2,12'-[6',10']methanocyclooct[b]indole] 3, a fused polycyclic structure derived from bicyclo[3.3.1]nonane, was accomplished via the Fisher indolization reaction. Enantiomers of this structure were obtained by chiral HPLC enantiomer separation on a swollen microcrystalline triacetylcellulose column. Chiroptical properties of the resolved enantiomers containing indole and 1,2-methylenedioxybenzene chromophores were studied. Application of the sector rule to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Optically active 2,9-dione, 3 , has been obtained by using chiral chromatography of racemic 3 9 and via asymmetric cyclization of an enamine of 2-(methoxymethyl)pyrrolidine. , Transparent spectral region specific rotations 9,18 and UV CD 9 have been reported. The AC of 3 was first determined by using the UV CD and the Octant Rule, with the result (1 R ,5 S )-(+)/(1 S ,5 R )-(−) .…”
Section: Introductionmentioning
confidence: 99%
“…Optically active 2,9-dione, 3 , has been obtained by using chiral chromatography of racemic 3 9 and via asymmetric cyclization of an enamine of 2-(methoxymethyl)pyrrolidine. , Transparent spectral region specific rotations 9,18 and UV CD 9 have been reported. The AC of 3 was first determined by using the UV CD and the Octant Rule, with the result (1 R ,5 S )-(+)/(1 S ,5 R )-(−) .…”
Section: Introductionmentioning
confidence: 99%
“…4 The angle between the planes of these chromophores in the minimized structure of 9 was found to be about 808 (Fig. 4 cf.…”
Section: Analysis Of the CD Spectramentioning
confidence: 97%
“…Recently it was demonstrated that the application of the sector rule to the 1,2-methylenedioxybenzene chromophore to establish the absolute configuration of the polycyclic compound did not lead to an unequivocal conclusion, which is likely to be due to the interaction of the chromophores. 4 Thus CD spectroscopy is not only a tool for studying the absolute configuration of organic molecules but also is a means to examine interactions between functional groups, i.e. chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…afforded the chiral [b] indole 585 in high yields (Scheme 130). 291 A couple of years later, another article from the same team unveiled the synthetic route toward a C 2 -symmetric methylenebridged product 588. This time, hydrazine 586 obtained from 4hydroxy-6-methyl-2(1H)-pyran-2-one 292,293 was treated with diketone 577, and the 2,9-diaza-3,10-dimethyl-1,8-dioxo-2,5,6,7,9,12,13,14octahydro-6,13methanocycloocta[1,2-b:5,6b ′ ] diindole 588 was obtained through the bishydrazone 587 (Scheme 131).…”
Section: Heterocyclizationmentioning
confidence: 99%
“…afforded the chiral 1′H-spiro [1,3-benzodioxole-2,12′-[6′,10′]methanocyclooct [ b ]indole 585 in high yields ( Scheme 130 ). 291 …”
Section: Reactivitymentioning
confidence: 99%